1983
DOI: 10.1128/jcm.17.5.898-905.1983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibody to Staphylococcus aureus teichoic acid by enzyme-linked immunosorbent assay

Abstract: A sensitive, specific, and rapid enzyme-linked immunosorbent assay has been developed for the detection of immunoglobulin G to Staphylococcus aureus teichoic acid in human sera. Detection of S. aureus teichoic acid antibody is at least 800 times more sensitive than a double diffusion in gel assay, and positive titers of 1:25,600 and greater were observed with this assay. Results with the enzyme-linked immunosorbent assay can be obtained within 3.5 h by using antigen-coated cuvettes. Quantitation of S. aureus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The results presented in this paper are in agreement with the findings of other authors who found the measurement of R-TA antibodies by CIE (3,6,10,13) or ELISA (5,16) useful in both the diagnosis and management of serious S. aureus infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented in this paper are in agreement with the findings of other authors who found the measurement of R-TA antibodies by CIE (3,6,10,13) or ELISA (5,16) useful in both the diagnosis and management of serious S. aureus infections.…”
Section: Discussionsupporting
confidence: 92%
“…Both techniques have limitations, and a better technique is badly needed (12). Recently, several enzyme-linked immunosorbent assay (ELISA) methods have been published, measuring antibodies against either staphylococcal R-TA (5,16) or peptidoglycan (14 This report gives details of a new ELISA for R-TA antibodies that has a number of advantages over CIE.…”
mentioning
confidence: 99%
“…A large number of serological assays for the diagnosis of serious S. aureus infections have been presented during the last decade most often using sensitive methods like RIA and ELISA. The cell wall antigens teichoic acid and peptidoglycan have been used most frequently (1, 3,10,12,14,16,17,18,19,21). A major problem is the lack of standardization in purifying the antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the difficulties associated with the isolation of the causative agent of osseous infections by routine bacteriological techniques, emphasis has been given recently to the development of serological assays as an aid to diagnosis. The techniques used for the serodiagnosis of serious staphylococcal infections have included gel diffusion (25,34), immunoelectrophoresis (11,25), radioimmunoassay (33,34), and the enzyme-linked immunosorbent assay ELISA (8,10,15,36). The most commonly used staphylococcal antigens for these assays are either ultrasonic preparations of whole cells, ribitol teichoic (TA) acid, or the peptidoglycan (PG) moiety of the cell wall.…”
mentioning
confidence: 99%